A randomised, double-masked phase III/IV study of the efficacy and safety of Avastin® (Bevacizumab) intravitreal injections compared to standard therapy in subjects with choroidal neovascularisation secondary to age-related macular degeneration: clinical trial design - Patel, Praveen J; Bunce, Catey; Tufail, Adnan (Current controlled trials in cardiovascular medicine, 2008)
Background The management of neovascular age-related macular degeneration (nAMD) has been transformed by the introduction of agents delivered by intravitreal injection which block the action of vascular endothelial growth factor-A (anti-VEGF agents). One such agent in widespread use is bevacizumab which was initially developed for use in oncology. Most of the evidence supporting the use of bevacizumab for nAMD has come from interventional case series and this clinical trial was initiated because of the increasing and widespread use of this agent in the treatment of nAMD (an off-label indication) despite a lack of definitive unbiased safety and efficacy data. Methods and design The Avastin ® (bevacizumab) for choroidal neovascularisation (ABC) trial is a double-masked randomised controlled trial comparing intravitreal bevacizumab injections to standard therapy in the treatment of nAMD. Patients are randomised to intravitreal bevacizumab or standard therapy available at the time of trial initiation (verteporfin photodynamic therapy, intravitreal pegaptanib or sham treatment). Ranibizumab treatment was not included in the control arm as it had not been licensed for use at the start of recruitment for this trial. The primary outcome is the proportion of patients gaining ≥ 15 letters of visual acuity at 1 year and secondary outcomes include the proportion of patients with stable vision and mean visual acuity change. Discussion The ABC Trial is the first double-masked randomised control trial to investigate the efficacy and safety of intravitreal bevacizumab in the treatment of nAMD. This trial fully recruited in November 2007 and results should be available in early 2009. Important design issues for this clinical trial include (a) defining the control group (b) use of gain in vision as primary efficacy end-point and (c) use of pro re nata treatment using intravitreal bevacizumab rather than continuous therapy. Trial registration Current controlled trials ISRCTN83325075